The apprenticeship of Big Toe P : - Matsuura, Rieko (Kodansha International, 2009)
The novel tells of a young Japanese woman who wakes up one afternoon to discover that her big toe has turned into a penis. In learning to adjust to her new sexual organ, the heroine is forced to reconsider her body, her sexuality and her life. After fleeing from her homophobic fiancé, she falls in love with a bisexual blind pianist who accepts her for whom she is, and together they join a troupe of performers--all sexually deformed and emotionally twisted men and women. Thus begins her apprenticeship